2000
DOI: 10.2307/3079019
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Asymmetry as a Bioindicator of Stress: Comparing Efficacy of Analyses Involving Multiple Traits

Abstract: Researchers have suggested fluctuating asymmetry (FA) as an indicator of environmental stress and have usually tested this assertion by examining relations between FA of single traits and stress. Fluctuating asymmetry stress relations are real but are typically weak and difficult to detect. Researchers would like to maximize the probability of detecting FA-stress relations when they exist. We assert that analyses based on the FA of multiple traits may provide better methods for detecting stress. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 0 publications
3
83
0
6
Order By: Relevance
“…In C. pipiens, Mpho et al (2002) reported evidence for an increase in wing FA with increase in temperature stress. However, and as hypothesized by Parsons (1992) and Leung et al (2000), this effect was only detected in extreme temperature conditions (Mpho et al 2002). The present experiment also shows that the detection of changes in FA required relatively severe environmental stress.…”
Section: Asymmetry Resistance Genes and Developmental Stresssupporting
confidence: 86%
“…In C. pipiens, Mpho et al (2002) reported evidence for an increase in wing FA with increase in temperature stress. However, and as hypothesized by Parsons (1992) and Leung et al (2000), this effect was only detected in extreme temperature conditions (Mpho et al 2002). The present experiment also shows that the detection of changes in FA required relatively severe environmental stress.…”
Section: Asymmetry Resistance Genes and Developmental Stresssupporting
confidence: 86%
“…Combining asymmetry measurements gives a better illustration of the effects of stressors (Leung et al, 2000) because it increases the statistical power and decreases the standard error of comparisons. Providing light during incubation was able to lessen the overall physical asymmetry (composite asymmetry) of the broilers in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Relative FA was used for all traits; it had distributions that were not normal and were transformed to arcsin square root before analysis. As an alternative to the analysis of FA based on the 4 single morphological traits, combined relative asymmetry was considered (defined as the mean of the relative asymmetries of the different traits); the analysis based on the combined FA may be a more reliable indicator of stress (Leung et al, 2000).…”
Section: Measurement Of Fa (10 Groups)mentioning
confidence: 99%